The Concept of the Fetus in Roman Law: between Hope and Inheritance - González Gutiérrez, Patricia (Gerión. Revista de Historia Antigua, 2017)
The mere existence of the fetus is a challenge to Roman law, since it involved an intersection between various family and personal rights, although it was not considered as a proper person. The various problems and solutions that appeared throughout Roman history allow us to approach the way they conceived society, the individual, family and gender constructions.